Kecukupan Udara Mempengaruhi Kenyamanan Pada Ruang Kamar - Syaidatul Maulianti; Zulfikar Ali As; Junaidi Junaidi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2021)
Ventilation is the process of exchanging clean air from outside into the room. Good ventilation is able to ensure smooth air circulation. This study aims to determine the relationship of air adequacy with comfort in room space. This research is an analytic study with cross sectional approach. The sample of this study was 30 rooms that used natural ventilation systems. The air change time is calculated from the volume of the room, the height and area of the ventilator, as well as the difference in the temperature of the outside and indoor air. Adequacy of air available with the air needed by its inhabitants. Objective comfort is based on the difference between outside and inside room temperature, and subjectively based on the room occupant's perspective. The results showed as many as 87% of the rooms had no air turnover time and as many as 20% of the rooms had insufficient air. Objectively stated rooms are uncomfortable as much as 57%, but subjectively reaching 77%. Statistically there is a significant relationship between air adequacy with comfort in the room objectively (p = 0.024). It can be concluded that the adequacy of the air represented by the ventilation system is related to the comfort of the air in the room space, to create a comfortable and healthy room space. Future research is expected to consider and include other factors that affect the ventilation system such as the layout of the furniture, the position of the ventilation, and the characteristics of the building so that research on comfort is more objective.